The culture of sparring training visits in the life of the Sigulai Tribe Lubuk Baik Village, Alafan Sub-District - Lasri, Lasri Lasri (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The culture of visiting is an activity of the Village Youth and PKK organizations that make visits to other villages both within one sub-district and outside the sub-district. In the culture of visiting, they practice sparring or playing football and volleyball. The culture of visiting can be beneficial for the community because these activities contain many cultural values. The problem in this study is how the positive and negative impacts of the culture of visiting on the lives of the Sigulai Tribe and how the strategy of maintaining the culture of visiting on the lives of the Sigulai Tribe. This research uses a qualitative method approach. The research instruments used were observation, interview, and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. The results showed that the positive impact of the culture of visiting can clearly support efforts to unite the community in youth organizations and PKK to establish a relationship between the community in visiting activities. In addition, negative impacts in this culture often also occur such as social deviance, juvenile delinquency during the merry night event, and physical violence during football and volleyball sparring games. The strategy in maintaining the culture of visiting by inviting the entire organization community to maintain, develop because there are many elements of goodness and values from the visiting activity